Selection, stability, and spuriousness: testing Gottfredson and Hirschi's propositions to reinterpret street gangs in self-control perspective - Pyrooz, David C. (Criminology, 2021)
Overlooked in the extensive literature on self-control theory are propositions with respect to street gangs. In Gottfredson and Hirschi's (1990) perspective, gangs are loose confederations of youth with low self-control and their criminological relevance is attributable to “politics and romance” rather than to rigorous empirical research. Prior research is limited by the use of cross-sectional data, which takes on added importance in light of recent findings on self-control instability. Using six waves of panel data from a large sample of youth, we test three propositions: gang membership is endogenous to self-control (selection), self-control is unrelated to gang membership (stability), and self-control confounds the well-established link between gang membership and delinquency (spuriousness). The main findings from stabilized inverse propensity-weighted multilevel structural equation models are that 1) self-control is one, but not the only, source of selection into gangs; 2) levels of self-control worsen during active periods of gang membership; and 3) gang membership maintains a direct association with delinquency, as well as an indirect association operating through self-control. The empirical evidence does not support reinterpreting gangs in self-control perspective, instead pointing to the continued relevance of the group context to criminology.